Plant quantum biology: The quantum dimension of plant responses to stress - Massimo E. Maffei (Plant Stress, 2025)
The intricate interplay of quantum coherence, entanglement, radical pair mechanisms, and tunneling, suggests that plants operate at a level of sophistication beyond classical expectations. The potential to harness these quantum principles for agricultural innovation and environmental sustainability is immense. This review provides a comprehensive overview of plant quantum biology, extending beyond photosynthesis and magnetosensitivity the exploration of enzyme catalysis and stress responses. The quantum coherence and entanglement in photosynthetic light harvesting and energy transfer, examining their role in efficient energy transduction is evaluated. Plant magnetosensitivity, mediated by cryptochromes and iron–sulfur clusters, is discussed as a potential quantum sensing mechanism. The radical pair mechanism influence on plant growth, development, and circadian rhythms via magnetic field perception is analyzed. Quantum tunnelling impact on enzyme reaction rates and substrate specificity is also discussed. The critical intersection of quantum biology and plant stress responses, encompassing light, oxidative stress, temperature, and biotic stress, is examined. How quantum effects might modulate these responses, offering opportunities for developing stress-tolerant crops reveal that challenges posed by biological complexity, transient quantum phenomena, and experimental limitations, along the need for robust theoretical models are future trends in plant stress biology. Future research should focus on manipulating quantum effects in vivo, bridging fundamental science and agricultural applications for enhanced sustainability.